2019
DOI: 10.4049/jimmunol.1900458
|View full text |Cite
|
Sign up to set email alerts
|

BTLA–HVEM Checkpoint Axis Regulates Hepatic Homeostasis and Inflammation in a ConA-Induced Hepatitis Model in Zebrafish

Abstract: The BTLA2HVEM checkpoint axis plays extensive roles in immunomodulation and diseases, including cancer and autoimmune disorders. However, the functions of this checkpoint axis in hepatitis remain limited. In this study, we explored the regulatory role of the Btla-Hvem axis in a ConA-induced hepatitis model in zebrafish. Results showed that Btla and Hvem were differentially expressed on intrahepatic Cd8 + T cells and hepatocytes. Knockdown of Btla or Hvem significantly promoted hepatic inflammation. Btla was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The eukaryotic expression vectors for Dr cGASa/b proteins with EGFP, Myc, Flag, and HA tags were constructed using pEGFP‐N1, pCMV‐N‐myc, pcDNA3.1‐EGFP‐Flag‐His, and pcDNA3.1‐EGFP‐HA‐His plasmids 31 . The point mutants of Dr cGASa/b prepared using a Quick Mutation Site‐Directed Mutagenesis Kit (Beyotime, Shanghai, China) were constructed into pcDNA3.1‐EGFP‐Flag‐His and pcDNA3.1‐EGFP‐HA‐His.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eukaryotic expression vectors for Dr cGASa/b proteins with EGFP, Myc, Flag, and HA tags were constructed using pEGFP‐N1, pCMV‐N‐myc, pcDNA3.1‐EGFP‐Flag‐His, and pcDNA3.1‐EGFP‐HA‐His plasmids 31 . The point mutants of Dr cGASa/b prepared using a Quick Mutation Site‐Directed Mutagenesis Kit (Beyotime, Shanghai, China) were constructed into pcDNA3.1‐EGFP‐Flag‐His and pcDNA3.1‐EGFP‐HA‐His.…”
Section: Methodsmentioning
confidence: 99%
“…After washing with PBS, cells were permeabilized with 0.1% Triton X‐100, blocked with 5% normal goat serum, and incubated with primary Abs or unrelated control IgG and secondary Abs at 4°C for 1 hour. Gill tissues were fixed in 4% paraformaldehyde overnight, and the paraffin sections were prepared as described 31 . After dewaxing the paraffin and retrieving Ags, the sections were blocked with 5% normal goat serum and incubated with primary Abs at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In a Con A challenge model of acute hepatitis, BTLA -/- mice showed reduced survival and increased early secretion of serum cytokines, which was partly due to the negative regulation of NKT cells by BTLA ( 65 ). Moreover, Shi et al discovered that BTLA could induce the self-tolerance of CD8 + BTLA + T cells to reduce the attack on hepatocytes, thus regulating hepatic homeostasis in a Con A-induced hepatitis model in zebrafish ( 66 ).…”
Section: The Functions Of Btla In Immune-related Diseasesmentioning
confidence: 99%
“…Recently, many investigations have focused on the relationship of BTLA with inflammation, autoimmune disease and cancer. Shi et al reported that BTLA-herpes virus entry mediator (HVEM) checkpoint axis might be implicated in the regulation of inflammation in liver [10]. A previous study indicated that the up-regulation of BTLA gene expression and soluble BTLA (sBTLA) was validated in thymoma-associated myasthenia gravis [11].…”
Section: Introductionmentioning
confidence: 99%